The Health and Health Insurance Implications of Climate Change in Sub-Saharan Africa: A Narrative Review - Ousmane Traoré; Jean Brice Tetka (Public Health Reviews)
ObjectivesThis paper aims to provide a narrative review of the implications of climate change on health and health insurance in sub-Saharan Africa.MethodsA comprehensive research was employed to carry out a complete narrative study on the subject. Thus, since September 2022 we searched for literature on the relationships between climate change, health, and health insurance on PubMed over an unbounded period. By updating the research method, the outputs cover the period 2009–2024.ResultsBased on 19 key articles that focused on the implications of climate change for health and health insurance in sub-Saharan Africa, we highlight that climate change directly affects population health through climate-related disease. Indirectly, climate change affects health through its disruption of food availability and agriculture and through demographic shifts.ConclusionFinally, this narrative review suggests appropriate strategies to combat the health consequences of climate change and to improve universal health insurance systems.